Light‐Gated Control of Conformational Changes in Polymer Brushes. Issue 4 (10th July 2021) - Bialas, Sabrina; Krappitz, Tim; Walden, Sarah L.; Kalayci, Kubra; Kodura, Daniel; Frisch, Hendrik; MacLeod, Jennifer M.; Nelson, Andrew; Michalek, Lukas; Barner‐Kowollik, Christopher
Abstract: Herein, a strategy to control conformational changes in grafted polymer brushes via photoinduced crosslinking of photoreactive groups embedded into the lateral architecture of a polymer brush is reported. Poly(methylmethacrylate)‐based polymer brushes containing UV‐light (λ = 325 nm) photoreactive o ‐methyl benzaldehyde moieties are synthesized using surface‐initiated reversible deactivation polymerization. The conformational changes in polymer brushes upon UV‐light triggered crosslinking are comprehensively analyzed through a full suite of surface sensitive characterization methods including time of flight secondary ion mass spectrometry, quartz crystal microbalance with dissipation monitoring, UV/vis spectroscopy, atomic force microscopy, nanoplasmonic sensing, and neutron reflectometry. The spatiotemporal control of the induced conformational changes is demonstrated via photolithography experiments. To enable an additional level of control, a second gate, the visible light (λ = 445 nm) active styrylpyrene moiety, is incorporated into the polymer brush architecture. Critically, wavelength‐selective crosslinking behavior is observed in the diblock copolymer structures allowing to crosslink specific sections of the lateral brush architecture as a function of irradiation wavelength. Abstract : Spatiotemporal control of polymer brush architectures can simply be achieved by light‐gated crosslinking chemistry. The polymer brush architecture is precisely controlled by predefined block structures and the additional incorporation of a second photochemical gate. The light‐gated surface pattern strategy can be readily applied as technology for tailoring surface properties in a spatially controlled fashion.